حساب بارامترات الخلايا الكهروضوئية من بيانات المصنع بتطبيق خوارزمية روزانبروك للحل الأمثل - نسمت أبوطبق (Tishreen University, 2019)
In this paper, a new technique based on Rosenbrock algorithm is proposed for determining the values of equivalent circuit elements of photovoltaic cell. The model with five parameters is considered. The Rosenbrock algorithm is applied as a tool for a nonlinear optimization problem with many physical constraints. To increase the probability of reaching the global minimum solution in a short time, the minimization of a quadratic objective function is used. The effectiveness of this approach is evaluated by MATLAB environment, the value of the objective function are around zero. The results prove that the Rosenbrock method is very suitable for estimating electrical parameters needed for modeling the PV array. اقترحنا في هذا المقال تقنية جديدة تعتمد على خوارزمية روزانبروك التكرارية بهدف تحديد قيم عناصر الدارة المكافئة للخلية الكهروضوئية. اعتمدنا هنا النموذج خماسي البارامترات. طبقنا خوارزمية روزانبروك كأداة لحل مسألة أمثلة لاخطية مع العديد من القيود الفيزيائية. لزيادة فرصة التوصل للقيمة الصغرى العامة للمسألة المطروحة بوقت قصير استخدمنا تابع هدف ذو صيغة تربيعية. أثبتت نتائج المحاكاة بمساعدة برنامج MATLAB فعالية الطريقة المقترحة حيث أن قيمة تابع الهدف المستخدم تتناهى فعلياً إلى الصفر. أي أن طريقة روزانبروك مناسبة جداً لحساب البارامترات الكهربائية المطلوبة لنمذجة اللوح الكهروضوئي.